2020
DOI: 10.3389/fmicb.2020.573388
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Calcium Signaling and Modulation of the LmrS Multidrug Resistant Efflux Pump Activity by Ca2 + Ions in S. aureus

Abstract: Calcium ions (Ca 2+) play a pivotal role in eukaryote cell signaling and regulate many physiological functions. Although a similar role for Ca 2+ in prokaryotes has been difficult to demonstrate, there is increasing evidence for Ca 2+ as a cell regulator in bacteria. The purpose of this study was to investigate Ca 2+ signaling and the effect of Ca 2+ on the Staphylococcus aureus multidrug resistant efflux pump LmrS. We hypothesized that antibiotics act by increasing Ca 2+ concentrations, which in turn enhance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 79 publications
1
14
0
Order By: Relevance
“…We have previously reported that overexpression of mdfA , a Na + -K + /H + antiporter of the major facilitator superfamily essential for alkaline tolerance in E. coli ( Lewinson et al, 2004 ), can compensate cell division defects and drug sensitivity of an E. coli strain lacking two partially redundant DedA family genes yqjA and yghB ( Kumar and Doerrler, 2014 ). In E. coli and S. aureus , alkaline pH was shown to induce calcium influx and cytoplasmic calcium accumulation compared to acidic pH ( Naseem et al, 2008 ; Nava et al, 2020 ). In light of these studies; it is possible that lower membrane potential of Δ dbcA at pH 7.5 is related to inefficient efflux of divalent cations at slightly alkaline pH.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that overexpression of mdfA , a Na + -K + /H + antiporter of the major facilitator superfamily essential for alkaline tolerance in E. coli ( Lewinson et al, 2004 ), can compensate cell division defects and drug sensitivity of an E. coli strain lacking two partially redundant DedA family genes yqjA and yghB ( Kumar and Doerrler, 2014 ). In E. coli and S. aureus , alkaline pH was shown to induce calcium influx and cytoplasmic calcium accumulation compared to acidic pH ( Naseem et al, 2008 ; Nava et al, 2020 ). In light of these studies; it is possible that lower membrane potential of Δ dbcA at pH 7.5 is related to inefficient efflux of divalent cations at slightly alkaline pH.…”
Section: Discussionmentioning
confidence: 99%
“…TelC is dependent on Ca 2+ ions for activity, as are many lipases including most previously characterised staphylococcal enzymes 10,50 . Calcium is abundant in the cell wall of staphylococci but is buffered in the cytoplasm at low micromolar levels 51,52 and we speculate that the concentration is too low to support intracellular TslA activity. In support of an extracellular activity for TslA, S. aureus coproduces an extracellular immunity lipoprotein, TilA for self-protection, which binds to TslA with a low nanomolar Kd.…”
Section: Discussionmentioning
confidence: 87%
“…When Mtb is phagocytosed by macrophages, tubercle bacilli then face an approximately 4-fold increase of the intraphagosomal Ca 2+ concentration at 24 h post-infection [ 15 , 57 ]. Cells respond to different environmental stimuli by transient changes in the cytosolic Ca 2+ concentration, which are useful to transmit information and to trigger cellular events according to the speed, timing and magnitude of the metal signal [ 26 , 58 ]. Some bacteria detect and respond to different environmental stimuli using two-component systems and Ca 2+ sensors, which transduce signals through phosphorylation events and protein–protein interactions and thereby regulate transcription and translation processes [ 27 , 59 ].…”
Section: Discussionmentioning
confidence: 99%